General conclusions - Teye, Alfred Larm (A+BE | Architecture and the Built Environment, 2018)
Since the 2007-2008 Global Financial Crisis (GFC), a great deal of research has been conducted in various countries into the dynamics and risks associated with house prices in an attempt to find innovative ways of reducing these risks and resuscitating a depressed housing market. This dissertation contributes to that literature by providing comprehensive analyses of the spatial diffusion and risks associated with house prices in the Netherlands. It also studies the efficiency and loss coverage of home-value insurance in the context of the Dutch housing market and suggests modifications to the index-based insurance scheme that would minimise the residual idiosyncratic risks for home-owners. The dissertation innovatively adopts empirical methods that combine standard statistical analyses with more complex and recent econometric models. The contributions of the dissertation are presented in five main chapters. Four of these chapters have already been published separately in international journals and one is under review. Chapter 2 provided a general overview of the Dutch housing market and the risks involved in home-ownership. Chapters 3, 4 and 5 were devoted to the diffusion mechanism of house prices in the Netherlands. Chapter 5 also dealt in part with house price risks, while Chapter 6 focused on the house price risks and home-value insurance. Each chapter has provided a detailed conclusion on each aspect of the research questions addressed in this dissertation. This concluding chapter summarises the main findings of the dissertation as a whole. The limitations of the analyses are discussed, together with potential applications for its findings and directions for further research.